PEMANFAATAN TEKNOLOGI DIGITAL MELALUI PENGEMBANGAN WEBSITE DESA DI DESA LATSARI, MOJOWARNO - Fitiara Ainur Rakhimah; Sofia Balqis Lesmana; Calvin Syamdhan Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The use of digital technology in village governance has become an effective way to enhance transparency, access to information, and community participation. This study aims to analyze the development and implementation process of a village website in Latsari Village, Mojowarno District, as an effort to leverage digital technology. The research method employed is a case study with a qualitative approach, involving in-depth interviews with village officials and local residents, as well as direct observation of the website development process. The findings indicate that the development of the village website has had a positive impact on strengthening communication between the village government and the community, improving budget management transparency, and facilitating access to public information. The community has also shown increased participation in village activities through this digital platform. However, challenges such as limited human resources and technological infrastructure remain obstacles to optimizing the village website. The study concludes that utilizing digital technology through the development of a village website can be a significant innovation in enhancing the effectiveness of public services at the village level. Recommendations are provided for other village governments to consider developing similar digital platforms as part of a more inclusive and transparent village development strategy.